The Influence of Operational Strategy, Content Marketing, and Cashback Program on Purchase Decisions at Mie Gacoan Restaurant Surabaya through the ShopeeFood Application - Nava Aurora Nabila; Saino Saino (Journal of Innovative and Creativity, 2025)
This research was motivated by preliminary findings among Mie Gacoan consumers in Surabaya, which revealed that flexible operational hours, visual promotional content, and cashback programs have significant potential to influence purchasing decisions through the Shopeefood application. The purpose of this study is to analyze the influence of operational strategy, Content Marketing, and cashback programs both partially and simultaneously on consumer purchasing decisions. This study employed a causal associative quantitative approach with an explanatory design and used purposive sampling involving 97 respondents who had made at least two purchases in the last three months. The results of multiple linear regression analysis showed that operational strategy had the most dominant influence (β = 0.589), followed by cashback programs (β = 0.281) and Content Marketing (β = 0.202), all of which had a positive and significant effect on purchasing decisions. Simultaneously, these three variables explained 52.1% of the variation in consumer purchase decisions (R² = 0.521). These findings emphasize the importance of integrating digital marketing strategies through operational services, visual promotions, and financial incentives in influencing consumer behavior in the digital food and beverage industry.